Reforming the Chimeric Antigen Receptor by Peptide Towards Optimized CAR T Cells With Enhanced Anti-Cancer Potency and Safety - Liu, Cuijuan; Li, Lin; Gao, Fan; Zhou, Jundong; Qin, Yingzhou; Yuan, Xin; Yang, Guang; Zhu, Yimin (Frontiers in Bioengineering and Biotechnology, 2022)
The emerging chimeric antigen receptor (CAR) T cell revolutionized the clinic treatment of hematological cancers, but meet its Waterloo in solid tumor therapy. Although there exist many reasons for this limitation, one of the largest challenges is the scarcity of recognition for tumor cells, resulting in the undesirable side effects and the subsequent ineffectiveness. To overcome it, a lung-cancer-cell-targeting peptide termed A1 was used in this work to reform the scFv domain of CAR by genetic manipulation. As a result, this modified A1CAR T exhibited the optimized cancer-cell targeting and cytotoxicity in vitro and in vivo. More importantly, by tuning the sensitivity of CAR to antigen, peptide-based A1CAR T cells could distinguish tumors from normal tissue, thereby eliminating the off-tumor toxicity in healthy organs. Collectively, we herein constructed a genetic peptide-engineered CAR T cells by inserting A1 peptide into the scFv domain. Profitted from the optimized recognition pattern and sensitivity, A1CAR T cells showed the ascendancy in solid tumor treatment. Our findings demonstrate that peptide-based CAR T holds great potential in solid tumor therapy due to an excellent targeting ability towards tumor cells.